Use of oxygen-loaded nanobubbles to improve tissue oxygenation: bone-relevant mechanisms of action and effects on osteoclast differentiation - Knowles, HJ; Vasilyeva, A; Sheth, M; Pattinson, O; May, J; Rumney, RMH; Hulley, PA; Richards, DB; Carugo, D; Evans, ND; Stride, E (Elsevier, 2023)
Gas-loaded nanobubbles have potential as a method of oxygen delivery to increase tumour oxygenation and therapeutically alleviate tumour hypoxia. However, the mechanism(s) whereby oxygen-loaded nanobubbles increase tumour oxygenation are unknown; with their calculated oxygen-carrying capacity being insufficient to explain this effect. Intra-tumoural hypoxia is a prime therapeutic target, at least partly due to hypoxia-dependent stimulation of the formation and function of bone-resorbing osteoclasts which establish metastatic cells in bone. This study aims to investigate potential mechanism(s) of oxygen delivery and in particular the possible use of oxygen-loaded nanobubbles in preventing bone metastasis via effects on osteoclasts. Lecithin-based nanobubbles preferentially interacted with phagocytic cells (monocytes, osteoclasts) via a combination of lipid transfer, clathrin-dependent endocytosis and phagocytosis. This interaction caused general suppression of osteoclast differentiation via inhibition of cell fusion. Additionally, repeat exposure to oxygen-loaded nanobubbles inhibited osteoclast formation to a greater extent than nitrogen-loaded nanobubbles. This gas-dependent effect was driven by differential effects on the fusion of mononuclear precursor cells to form pre-osteoclasts, partly due to elevated potentiation of RANKL-induced ROS by nitrogen-loaded nanobubbles. Our findings suggest that oxygen-loaded nanobubbles could represent a promising therapeutic strategy for cancer therapy; reducing osteoclast formation and therefore bone metastasis via preferential interaction with monocytes/macrophages within the tumour and bone microenvironment, in addition to known effects of directly improving tumour oxygenation.